2011
DOI: 10.1159/000324694
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Glomerular Injury in Diabetic Mice with Tert-Butylhydroquinone through Nuclear Factor Erythroid 2-Related Factor 2-Dependent Antioxidant Gene Activation

Abstract: Background/Aims: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a positive regulator of the expression of antioxidant genes. This study is aimed at examining the effect of tert-butylhydroquinone (tBHQ), an activator of Nrf2, on hyperglycemia-related diabetic nephropathy. Methods: CD-1 mice were induced with streptozotocin and treated with 1% tBHQ, or omitting it, in their diet for 12 weeks. Four and twelve weeks later, the levels of serum and glomerular malondialdehyde (MDA), blood glucose, kidney and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 46 publications
0
38
1
Order By: Relevance
“…Several studies have explored the protective effect of tBHQ. Oral administration of tBHQ prevented glomerular injury in diabetic mice (Li et al, 2011). Moreover, pre-treatment with tBHQ also protected mice brains against traumatic brain injury-induced inflammatory damage (Jin et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have explored the protective effect of tBHQ. Oral administration of tBHQ prevented glomerular injury in diabetic mice (Li et al, 2011). Moreover, pre-treatment with tBHQ also protected mice brains against traumatic brain injury-induced inflammatory damage (Jin et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…26 Many studies have reported the important role of tBHQ as a dietary antioxidant in preventing oxidative damage caused by active oxygen radicals in living systems. [27][28][29] Reactive oxygen species (ROS) participate in atherogenesis through different mechanisms, including oxidative stress and inflammation, which can be reduced by antioxidants. 30 Recent research suggests that a tBHQ diet increases the expression of LDL-related protein-1, a multi ligand endocytotic receptor involved in transporting amyloid-beta peptide out of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding diabetic mice a diet containing 1% tBHQ significantly reduced the levels of serum and glomerular malondialdehyde, kidney weight and proteinuria, as well as decreased levels of fibronectin while concomitantly increasing Nrf2 protein expression and nuclear accumulation and expression of HO-1 and γ-GCS [8].…”
Section: Targeting Keap1-nrf2 Dysregulationmentioning
confidence: 95%
“…The antioxidants sulforaphane (SFN) and tetrahydroxyquinone (tBHQ) disrupt the Keap1-Nrf2 complex and have been shown to be effective in reducing or preventing diabetic complications by increasing Nrf2 content and activity in animal models [8,11,44]. It was originally believed that SFN and tBHQ increased Nrf2 activity by modifying cysteine residues of the Nrf2-Keap1 complex and caused dissociation in a manner similar to ROS [32].…”
Section: Targeting Keap1-nrf2 Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation